2009
DOI: 10.1111/j.1469-1809.2009.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA and Family Relationships in a Pompeian House

Abstract: SummaryArchaeological, anthropological and pathological data suggest that thirteen skeletons found in a house at the Pompeii archaeological site, dated to 79 A.D., belong to one family. To verify this and to identify the relationships between these individuals, we analyzed DNA extracted from bone specimens. Specifically, hypervariable segment 1 (HVS1) of the human mitochondrial DNA (mtDNA) control region was amplified in two overlapping polymerase chain reactions and the sequences were compared to the revised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…As control, we analysed two bone remains belonging to skeletons found in Caius Iulius Polybius house in Pompeii (79 A.D.), whose molecular data were previously reported [24, 25]. Bone samples were treated to avoid contamination as already described [25]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As control, we analysed two bone remains belonging to skeletons found in Caius Iulius Polybius house in Pompeii (79 A.D.), whose molecular data were previously reported [24, 25]. Bone samples were treated to avoid contamination as already described [25]. …”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from ancient samples using a previously reported procedure [25, 26] with slight modifications. One hundred milligrams of bone powder was demineralized in 1.5 mL of EDTA 0.5 M (pH 8.0) and 100  μ L of 20 mg/mL proteinase K in a rotary shaker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and equine Pompeian remains were also successfully investigated to prove the presence of ancient DNA within the osteocytic lacunae by means of histochemical methods (Guarino et al, 2000(Guarino et al, , 2006. Finally, a new molecular study on the thirteen skeletons found in the House of Polybius in Pompeii revealed that six individuals were genetically closely related (Di Bernardo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Favorable aDNA preservation due to burial conditions was also shown by Bailey et al (1999), who extracted DNA from a young Barbary macaque from the Sarno Baths in Pompeii. More recently, analysis of mitochondrial and nuclear DNA fragments was performed on five equids discovered in Pompeii within the House of the Chaste Lovers and on an equid found in the archaeological site of Herculaneum, thus allowing the taxonomical status of these equids to be tested (Di Bernardo et al, 2004a, 2004b. Human and equine Pompeian remains were also successfully investigated to prove the presence of ancient DNA within the osteocytic lacunae by means of histochemical methods (Guarino et al, 2000(Guarino et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%